Relation between anatomical features of patent foramen ovale and residual shunt based on transesophageal echocardiography - Zeyu Mi; Chao Li; Gang He; Daxin Huang; Xiangwei Zhou; Hongli Gao; Deyu Yang; Yulin Hu (Scientific Reports)
Abstract We aimed to evaluate the incidence of residual shunt after patent foramen ovale (PFO) closure and analyze the anatomical features of PFO to determine the risk factors for significant residual shunt after PFO closure. Ninety-two patients who underwent PFO closure at our center between September 2021 and June 2022 were consecutively enrolled. Transthoracic saline contrast echocardiography was performed at 6 and 12 months postoperatively to evaluate the presence of a significant residual shunt. Preoperative measurements of the anatomical structures of PFO were performed using transesophageal echocardiography. Binary logistic regression analysis was performed to determine the risk factors for significant residual shunt at 12 months after PFO closure, and receiving operating characteristic curves were plotted to calculate the cutoff values. At the follow-up 12 months postoperatively, 22 (24%) of the 92 patients showed significant residual shunt. Thicker secondary septum and longer tunnel were independent risk factors for significant residual shunt after PFO closure. In particular, patients with secondary septum thickness > 6.55 mm or tunnel length > 10.10 mm were more susceptible to significant residual shunt. This study may guide clinicians in developing individualized PFO treatment strategies.